P696 HIV among female sex workers and clients in the middle east and north africa: subregional differences and epidemic potential. (14th July 2019) - Chemaitelly, Hiam; Weiss, Helen; Calvert, Clara; Harfouche, Manale; Abu-Raddad, Laith
Abstract : Background: This study addresses the gap in our understanding of HIV epidemiology among female sex workers (FSWs) and clients in the Middle East and North Africa (MENA) region. Methods: An exhaustive systematic review of population-size estimation and of HIV prevalence studies was conducted. Findings were reported following PRISMA guidelines. The pooled mean HIV prevalence was estimated using random-effects meta-analyses. Associations with prevalence, sources of heterogeneity, and temporal trends were investigated using meta-regressions. Results: We identified 270 size-estimation studies in FSWs and 42 in clients, as well as 485 HIV prevalence studies on 287, 719 FSWs, and 69 on 29, 531 clients/proxy populations (male sexually transmitted infections clinic attendees). The median proportion of reproductive-age women reporting current/recent sex work was 0.7% (range=0.2–2.4%), and of men reporting currently/recently buying sex was 5.7% (range=0.3–13.8%). HIV prevalence ranged from 0-70% in FSWs (median=0.1%), and 0–34.6% in clients (median=0.4%). The regional pooled mean HIV prevalence was 1.4% (95% CI=1.1–1.8%) in FSWs and 0.4% (95% CI=0.1–0.7%) in clients. Country-specific pooled HIV prevalence in FSWs was <1% in most countries, 1–5% in North Africa and Somalia, 17.3% in South Sudan, and 17.9% in Djibouti. Meta-regressions identified strong subregional variations in prevalence, where compared to Eastern MENA, the adjusted odds ratios (AORs) ranged from 0.2 (95% CI=0.1–0.4) in Fertile Crescent to 46.3 (95% CI=25.9–82.6) in Horn of Africa. There was also strong evidence for increasing prevalence post-2003, at a rate of 14% per year (AOR=1.14, 95% CI=1.08–1.20). Conclusion: HIV epidemics among FSWs are emerging in MENA, with some already in an established phase, though still some countries have limited epidemic dynamics. The epidemic has been growing for over a decade, with strong regionalization and heterogeneity. Disclosure: No significant relationships.